Anti-inflammatory and analgesic properties of Moroccan medicinal plants: Phytochemistry, in vitro and in vivo investigations, mechanism insights, clinical evidences and perspectives - Abdelhakim Bouyahya; Fatima-Ezzahrae Guaouguaou; Nasreddine El Omari; Naoual El Menyiy; Abdelaali Balahbib; Mohamed El-Shazly; Youssef Bakri (Elsevier, 2022)
Moroccan medicinal plants exhibit several pharmacological properties such as antimicrobial, anticancer, antidiabetic, analgesic, and anti-inflammatory effects, which are related to the presence of numerous bioactive compounds, including phenolic acids, flavonoids, and terpenoids. In the present review, we systematically evaluate previously published reports on the anti-inflammatory and analgesic effects of Moroccan medicinal plants. The in vitro investigations revealed that Moroccan medicinal plants inhibit several enzymes related to inflammatory processes, whereas in vivo studies noted significant anti-inflammatory and analgesic effects as demonstrated using different experimental models. Various bioactive compounds exhibiting in vitro and in vivo anti-inflammatory and analgesic effects, with diverse mechanisms of action, have been identified. Some plants and their bioactive compounds reveal specific secondary metabolites that possess important anti-inflammatory effects in clinical investigations. Our review proposes the potential applications of Moroccan medicinal plants as sources of anti-inflammatory and analgesic agents.